Planejamento de rotas dirigidas com base no problema de roteamento humano - Rodrigues, Rafael Emidio Murata (2018)
In our lives, we constantly move in streets and neighborhoods. In general, we consider time and (or distance) when planning the route. However, their solutions may face complex problems arising from the different possibilities of solutions. Similar to route planning, the Vehicle Routing Problem was introduced by George B. Dantzig and John H. Ramser in 1959 and consists of delivering gasoline to several fuel stations; at first a mathematical proposal, later became an algorithmic approach, for planning of routes of delivery of products in an optimized way (searching the "shortest path"). Although, during the search of shortest path, they are limited to the use of the streets. In this context emerges the Human Routing Problem, such an approach is not limited to streets, but makes use of all possible paths, by vehicles and humans. Such a problem can be observed in route planning at airports, museums and a supply chain company that wants to optimize the route of delivery of its products and increase customer satisfaction. Based on the Vehicle Routing Problem, the Human Routing Problem will be proposed. Its problematic will be demonstrated in a prototype, capable of assisting in the planning of human routes and three use cases. Ideas of Human Routing Problem had inspiration in the collective foraging insects